Social class - Patton, Ken; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1971)
Shows the shooting process in production of film and motion pictures
Note: 1p.
Converted into VHS 1/2 in.
Title from title screen
Executive producer, John Radcliffe
Keywords: Social classes; Social role